2015
DOI: 10.1044/2015_jslhr-l-14-0131
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Phonomotor Treatment on Word Retrieval Abilities in 26 Individuals With Chronic Aphasia: An Open Trial

Abstract: The results of this trial demonstrate generalization of training effects on laboratory measures, which were sustained at 3 months, and provide support for the theories that motivated the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…Treatment studies have demonstrated that generalisation across behaviours increases when there is a hierarchical relationship between trained and untrained targets (eg, within category generalisation from abstract words to concrete words, 51 when more complex words or sentences are selected for treatment of word finding or syntax, respectively 6 52 and when trained words or sentences engage common linguistic rules or principles. s38, s39 Furthermore, generalisation across tasks occurs when the tasks share psycholinguistic mechanisms (eg, training novel phoneme sequences to strengthen the phonological system can generalise to improvements in word retrieval 53 and reading.) 54 Improvements in discourse, which are important for generalisation across contexts, have been found in approaches that treat longer utterances, such as CILT 55 and verb network strengthening treatment.…”
Section: Principles For Inducing Beneficial Neuroplasticity Through Amentioning
confidence: 99%
“…Treatment studies have demonstrated that generalisation across behaviours increases when there is a hierarchical relationship between trained and untrained targets (eg, within category generalisation from abstract words to concrete words, 51 when more complex words or sentences are selected for treatment of word finding or syntax, respectively 6 52 and when trained words or sentences engage common linguistic rules or principles. s38, s39 Furthermore, generalisation across tasks occurs when the tasks share psycholinguistic mechanisms (eg, training novel phoneme sequences to strengthen the phonological system can generalise to improvements in word retrieval 53 and reading.) 54 Improvements in discourse, which are important for generalisation across contexts, have been found in approaches that treat longer utterances, such as CILT 55 and verb network strengthening treatment.…”
Section: Principles For Inducing Beneficial Neuroplasticity Through Amentioning
confidence: 99%
“…We note that there are other accounts of lexical knowledge based on connectionist spreading-activation frameworks in which parallel activation occurs throughout lexical processing (e.g., Kendall, Oelke, Brookshire, & Nadeau, 2015), and thus there may not be a staged component to these accounts. A full evaluation of these proposals and how they relate to the present data or the other lexical access data addressed by the frameworks discussed above is outside of the scope of this article.…”
Section: Interactivity In Spoken Productionmentioning
confidence: 99%
“…Specifically, damage to left perisylvian cortical areas typically weakens representation and processing of phonemes and phoneme sequences. 5,6 This type of injury often results in aphasia. Individuals with aphasia and phonological impairment are known to have difficulty with sound sequencing and produce phonemic paraphasias (e.g., saying speen for spoon).…”
Section: Contribution Of Phonology To Language Processingmentioning
confidence: 99%
“…Phonomotor treatment is one such word retrieval treatment that specifically targets phonological processing and phonological regularities (or phoneme sequence knowledge). 6,12,37 PHONOMOTOR TREATMENT Phonomotor treatment is a multimodal treatment for phonology that was inspired by the Lindamood Phoneme Sequencing Program for Reading, Spelling, and Speech and adapted for individuals with aphasia. 38 The theoretical motivation behind phonomotor treatment, a connectionist, parallel distributed processing (PDP) model of phonology, 11 has been discussed in-depth elsewhere and will only be briefly reiterated here.…”
Section: Traditional Phonological Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation